2021
DOI: 10.1159/000517922
|View full text |Cite
|
Sign up to set email alerts
|

Focused Neck Ultrasound and Lymph Node Sampling by Respiratory Physicians in Suspected Lung Cancer

Abstract: <b><i>Background:</i></b> Malignant cervical lymphadenopathy in the setting of lung cancer represents N3 disease, and neck ultrasound (NUS) with sampling is described in the Royal College of Radiologists ultrasound training curriculum for the non-radiologists. This study reviews the incorporation of NUS +/− biopsy in the routine practice of a lung cancer fast-track clinic in the UK. <b><i>Methods:</i></b> We retrospectively assessed 29 months of activity of a lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Additional TUS in the Workup of Patients with Unilateral Pleural Effusion suspected lung cancer [14] and a high diagnostic yield of instant ultrasound-guided biopsies [15]. In our study, a minority were diagnosed with lung cancer, while several patients had mesothelioma where spread to cervical lymph nodes is rare [16].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Additional TUS in the Workup of Patients with Unilateral Pleural Effusion suspected lung cancer [14] and a high diagnostic yield of instant ultrasound-guided biopsies [15]. In our study, a minority were diagnosed with lung cancer, while several patients had mesothelioma where spread to cervical lymph nodes is rare [16].…”
Section: Discussionmentioning
confidence: 54%
“…We did not find any cases of enlarged infraclavicular, supraclavicular, or cervical lymph nodes. Previous studies have found a high prevalence of ultrasound-verified enlarged cervical lymph nodes in patients with suspected lung cancer [ 14 ] and a high diagnostic yield of instant ultrasound-guided biopsies [ 15 ]. In our study, a minority were diagnosed with lung cancer, while several patients had mesothelioma where spread to cervical lymph nodes is rare [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main limitations of our evaluation were that the retrospective design incorporates operator selection bias in the decision-making to both select the patient for EBUS and proceed to sampling intraprocedurally. In addition, suspected lung cancer patients are increasingly screened for the percutaneous US-guided sampling from accessible lymph nodes, lung, chest wall, and anterior mediastinum, if an alternative target is present 24,25. This may have contributed to the small proportion of intrapulmonary tumor sampling we observed at our center as this is undertaken routinely at our center.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, suspected lung cancer patients are increasingly screened for the percutaneous US-guided sampling from accessible lymph nodes, lung, chest wall, and anterior mediastinum, if an alternative target is present. 24,25 This may have contributed to the small proportion of intrapulmonary tumor sampling we observed at our center as this is undertaken routinely at our center. Finally, we identified complications retrospectively which may have underestimated rates.…”
Section: Discussionmentioning
confidence: 99%
“…Hassan et al ( 20 ) reported a CNB positive diagnostic rate of 82.6% in cases with suspected cervical lymph node metastasis of lung cancer. Elsewhere, Oh et al ( 21 ) studied the sensitivity and specificity of CNB in the diagnosis of cervical lymph node metastasis and found them to be 91.6% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%